The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1094/mpmi-09-15-0209-r
|View full text |Cite
|
Sign up to set email alerts
|

A Fungal Effector With Host Nuclear Localization and DNA-Binding Properties Is Required for Maize Anthracnose Development

Abstract: Plant pathogens have the capacity to manipulate the host immune system through the secretion of effectors. We identified 27 putative effector proteins encoded in the genome of the maize anthracnose pathogen Colletotrichum graminicola that are likely to target the host's nucleus, as they simultaneously contain sequence signatures for secretion and nuclear localization. We functionally characterized one protein, identified as CgEP1. This protein is synthesized during the early stages of disease development and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 85 publications
1
45
0
Order By: Relevance
“…In our study, neither SignalP nor WoLF PSORT indicated the presence of a signal peptide in this protein. A second candidate nuclear effector identified in [79], GLRG_03517, was similarly not predicted to have a signal peptide in our study. A third putative NLS effector from that study (GLRG_08510) was on our list of NCPs as a predicted SSP, but not as a nuclear protein.…”
Section: Resultsmentioning
confidence: 50%
See 2 more Smart Citations
“…In our study, neither SignalP nor WoLF PSORT indicated the presence of a signal peptide in this protein. A second candidate nuclear effector identified in [79], GLRG_03517, was similarly not predicted to have a signal peptide in our study. A third putative NLS effector from that study (GLRG_08510) was on our list of NCPs as a predicted SSP, but not as a nuclear protein.…”
Section: Resultsmentioning
confidence: 50%
“…Some of these NCPs may also specifically target the host nucleus: for example, one of the predicted nuclear proteins in C. graminicola was GLRG_04079, aka. CgEP1, recently characterized as an essential C. graminicola effector that is targeted to the plant nucleus, with both a secretion signal and a nuclear localization signal (NLS) [79] (Additional file 5: Table S4). In our study, neither SignalP nor WoLF PSORT indicated the presence of a signal peptide in this protein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of them were also found in the Fg exudates (fuGraFG1chr3G262700.1, fuGraFG1chr1G376300.1, and FGSG_03017) and two showed significant abundance changes during the infection (fuGraFG1chr2G224300.1 and fuGraFG1chr3G262700.1). Fungal proteins can be located in the plant nucleus to drive the success of the disease (Robin et al, ; Vargas et al, ). Such Fg proteins could partly explain the significant enrichment in wheat of FHB‐regulated proteins involved in nucleic acid binding and in translation.…”
Section: Discussionmentioning
confidence: 99%
“…Another criterion used to identify putative effectors from obligate intracellular pathogens has been the presence of nuclear localization domains, which allows effectors to directly modulate plant gene expression [58,59]. For many years, effectors capable of migrating to the plant cell nucleus have only been described in bacteria [5860], but more recently these motifs together with nuclear localization of effectors has been described in fungi [61,62] and nematodes [63]. In bioinformatics pipelines designed to identify putative effectors, the inclusion of steps to remove proteins containing subcellular localization signals will remove these effectors, although researchers could analyze these amino acid sequences directly using the online tool TargetP 1.1 Server (http://www.cbs.dtu.dk/services/TargetP).…”
Section: Where and How To Look For Effectors?mentioning
confidence: 99%